Floristic composition of Peruvian plantcutter (Phytotoma raimondii) habitat - Romo, Mónica (2012)
Through of the analysis of the floristic composition of 16 plots of half an hectare in 12 sites where the Phyto-toma raimondii, Peruvian plantcutter exists, we found that richness and diversity of plants are not related to the abundance of the bird, neither the abundance of any of the 7 species used as food or for nestting, except the algarrobo (Prosopis pallida). The most frequent species in the 12 sites were algarroboProsopis pallida(92% of the sites), vichayoCapparis ovalifolia(67%), canutilloGrabowskia boerhaviifolia(58%), sapoteCapparis scabrida(58%) and realengoMaytenus octogona(25%). Besides algarrobo, canutillo seem to be a key species because in the plots where only three species occurred, those two were present. In the plots where canutillo was present, realengo did not more than expected statistically. It is alarming the decrease and few places or habitats for the occurrence and reproduction of the Peruvian plantcutter, a species considered in danger of extinction.